UTILIZATION OF VILLAGE POTENTIAL FOR SUSTAINABLE TOURISM DEVELOPMENT IN BELITAR SEBANG VILLAGE - Gilang Dovia Carles; Hajar Gelis Pramudyasmon; Diyas Widiyarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Sustainable tourism development still often uses a needs-based approach, so it does not optimize the assets that local communities already have. This study aims to analyze the strategy of utilizing local potential through the Asset-Based Community Development (ABCD) approach in building sustainable tourist destinations in Belitar Sebang Village. A descriptive qualitative research method with a case study strategy was applied, where data was collected through observation, in-depth interviews, and documentation studies. The results of the study identified three strategic asset clusters, namely unique natural assets (such as the dichotomy of hot and cold waterfalls), living cultural assets (including the art of Kuda Lumping and palm sugar production), and artificial assets that are integrated with the environment. The scientific contribution of this research lies in the provision of an ABCD-based analytical framework that integrates the dichotomous assets of nature and culture as the foundation of destination competitiveness. The study's conclusions show that development effectiveness is highly dependent on collaborative governance that empowers all local assets, where the ABCD approach offers a relevant conceptual foundation for achieving economic and socio-cultural sustainability